2002
DOI: 10.1142/s0217979202015340
|View full text |Cite
|
Sign up to set email alerts
|

ICP ETCHING AND STRUCTURE STUDY OF PECVD SiC FILMS

Abstract: Results of Induction Coupled Plasma (ICP) etching of as-prepared and annealed PECVD hydrogenated amorphous silicon carbide (a-Siix C x :H) films using CF4/O2 chemistry are presented. The etch rate of the annealed films decreased with an increase in annealing temperature. Infrared spectra for the annealed films showed a significant decrease in the Si-H and C-H bonds, and a pronounced increase in the Si-C bonds. The XRD results showed several poly-crystalline Si-C structure in films annealed at 800°C. ESR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…While sol–gel TiO 2 is amorphous, sputtered and thermal TiO 2 have crystalline structures. It appears that the etching rate of amorphous structures seems to be greater than that of crystalline structures, which is consistent with the earlier findings by Shi et al . Regarding the greater resistance of thermal TiO 2 to etching than sputtered TiO 2 , we ascribe this property to the annealing temperature or the phase of the TiO 2 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While sol–gel TiO 2 is amorphous, sputtered and thermal TiO 2 have crystalline structures. It appears that the etching rate of amorphous structures seems to be greater than that of crystalline structures, which is consistent with the earlier findings by Shi et al . Regarding the greater resistance of thermal TiO 2 to etching than sputtered TiO 2 , we ascribe this property to the annealing temperature or the phase of the TiO 2 .…”
Section: Resultssupporting
confidence: 92%
“…On the basis of these XRD spectra, we found that the sputtered TiO 2 exists in the anatase phase (annealed at 400 °C in 4 h), whereas the phase of the thermal TiO 2 is rutile (annealed at 500 °C in 8 h). Shi et al claimed that the improvement of crystallinity after annealing results in a stronger bonded network, lowering the etch rate . In the experiment, the sol–gel TiO 2 samples are best for tuning hydrophobic behaviors of TiO 2 layers because ICP etching has a greater impact on the morphology change of the sol–gel TiO 2 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation